LIQUIDITY, SOLVABILITY AND FINANCIAL PERFORMANCE (STUDY ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE) - Peni Moegi Lestari; Kartika Hendra Titisari; Istiatin Istiatin (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2021)
Good company performance will be able to help management in achieving the company's goals. The higher the company's performance, the better the company's value in the eyes of investors. Assessment of the company's financial performance is one of the ways that management can meet its obligations to funders and also achieve the goals set by the company. The purpose of this study is to test and analyze the effect of liquidity, debt to assets ratio solvency and equity ratio affect the profitability of Return On Assets of manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. This research data is panel data  where panel data is a combination of cross section and time series. The samples in this study were nine pulp and paper sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. Data analysis techniques using panel data regression analysis. The results explain that the liquidity ratio calculated by cash ratio has no significant effect on financial performance. The solvency ratio calculated by the Debt to Assets Ratio affects financial performance. The solvency ratio calculated by the Debt to Equity Ratio affects the company's financial performance.